Curriculum Design for the Applied Undergraduate Business Information System Study Program: Focus on learning Outcomes required in Indonesia - Meyti Eka Apriyani; Agung Nugroho Pramudhita; Indra Dharma Wijaya (Nusantara Science and Technology Proceedings, 2022)
In Industry 4.0, where the internet and information technology have become primary needs, it is necessary to integrate information technology with the world of business and industry. The business world and industry need new skills. Higher Education, especially polytechnics as producers of expert workers, has not produced many graduates with competencies that are relevant to current conditions. Therefore, a curriculum is needed that can create graduates suitable for the needs of the business and industrial world. This research aims to design an integrated curriculum between business and industry that will be applied in the Applied Bachelor Program in Business Information Systems at the State Polytechnic of Malang. Qualitative research methods were used in this study, and literature studies and discussions were carried out with several industry curriculum experts and practitioners from the industry. The redesigned curriculum requires several analyses such as several data sources, namely curriculum evaluation which contains analysis from the previous curriculum, study materials or literature study and input from industry through tracer studies. The curriculum is made by paying attention to pedagogical learning and integrating industry, business and informatics. The redesigned curriculum also pays attention to the body of knowledge (BOK) by taking similar knowledge covering four main areas: information system strategy and management, information system development, operation, and evaluation of information system solutions. The results of this study are in the form of graduate profiles and a learning outcome matrix that is following the study material and the integration between business and informatics for applied undergraduate polytechnics.